Tin-bronze cladding on thin steel sheet by cold metal transfer arc deposition. Issue 12 (13th August 2019) - Chen, Chen; Xu, Qiman; Sun, Kai; Zhao, Jingyu; Zhou, Jian; Xue, Feng
ABSTRACT: Tin bronze cladding layer with thin thickness and large width was fabricated on thin steel sheet by cold metal transfer arc deposited technique. The morphology, microstructure and mechanical properties of both cladding layer and thin steel sheet were investigated. It was found that the cladding layer had no gas holes, cracks, oxide particles and iron-rich phase. The thickness of diffusion layer at tin bronze/steel interface was only 3–4 µm and the dilution rate of the cladding layer was almost zero. The strength and hardness of the thin steel sheet after arc deposited process were enhanced.